Conceptualizing rurality: The impact of definitions on the rural mortality penalty - James, Wesley L.; Brindley, Claire; Purser, Christopher; Topping, Michael (Frontiers in Public Health, 2022)
Background In the U.S., inequality is widespread and still growing at nearly every level conceivable. This is vividly illustrated in the long-standing, well-documented inequalities in outcomes between rural and urban places in the U.S.; namely, the rural mortality penalty of disproportionately higher mortality rates in these areas. But what does the concept of “rural” capture and conjure? How we explain these geographic differences has spanned modes of place measurement and definitions. We employ three county-level rural-urban definitions to (1) analyze how spatially specific and robust rural disparities in mortality are and (2) identify whether mortality outcomes are dependent on different definitions. Methods We compare place-based all-cause mortality rates using three typologies of “rural” from the literature to assess robustness of mortality rates across these rural and urban distinctions. Results show longitudinal all-cause mortality rate trends from 1968 to 2020 for various categories of urban and rural areas. We then apply this data to rural and urban geography to analyze the similarity in the distribution of spatial clusters and outliers in mortality using spatial autocorrelation methodologies. Results The rural disadvantage in mortality is remarkably consistent regardless of which rural-urban classification scheme is utilized, suggesting the overall pattern of rural disadvantage is robust to any definition. Further, the spatial association between rurality and high rates of mortality is statistically significant. Conclusion Different definitions yielding strongly similar results suggests robustness of rurality and consequential insights for actionable policy development and implementation.